Fibulin-3 in plasma and pleural effusion as a biomarker of mesothelioma - Adamič, Katja (Radiology and oncology (Ljubljana), 2025)
Background: Malignant pleural mesothelioma (MPM) is a global health concern linked to asbestos exposure. In Slovenia, regions with high asbestos exposure rates make MPM a significant public health issue. Although thoracoscopic biopsy is the gold standard for MPM diagnosis, its invasiveness highlights the need for reliable, non-invasive diagnostic biomarkers. Patients and Methods: This prospective study evaluated the diagnostic potential of fibulin-3 as a biomarker for MPM, focusing on its ability to distinguish MPM from other pleural conditions, its association with disease stage and histological subtype, and its prognostic value for survival. 90 patients who underwent diagnostic thoracoscopic biopsy from January 2013 to October 2014 were included. Fibulin-3 levels in plasma and pleural effusion were measured using ELISA, and clinical data were analysed with statistical tests, including ROC analysis. Results: The study cohort comprised 32 patients with MPM, 24 with metastatic pleural carcinoma, and 34 with benign pleural diseases. Plasma fibulin-3 levels were significantly elevated (p = 0.0132) in MPM patients compared to those with benign pleural effusions due to asbestos exposure, with a cut-off of 12.31 ng/mL showing 100% specificity but low sensitivity (39.39%). Elevated fibulin-3 levels in pleural effusion correlated with advanced disease (p = 0.0463) and aggressive histological subtypes (p = 0.0324). No significant survival correlation was observed. Conclusions: While plasma fibulin-3 is a highly specific biomarker for MPM, its low sensitivity limits its standalone diagnostic utility. Its potential role in risk stratification and early detection in at-risk populations warrants further study.
Keywords: Azbest; biomarker; Biomarkerji; Biomarkers; fibulin-3; Malignant; maligni; Mesothelioma; Mezoteliom; Ocena tveganja; Plevralni izlivi; Risk Assessment